Comparing the effect of addition of different supplements to sperm preparation media on intracytoplasmic injection outcome - Mohamed Ashraf Adly; Ahmed Samy Saad; Amoura Abou-El-Naga (Journal of Basic and Applied Zoology)
Abstract Background  To assess the effectiveness of human sperm treated with an egg yolk-enhanced refrigeration group and to determine the protective effect of selenium supplementation in a laboratory setting, samples were prepared using the density gradient method as the standard preparation technique. Additionally, the study aimed to investigate how these treatments affected the outcomes of intracytoplasmic sperm injection (ICSI). This randomized, double-blind, placebo-controlled clinical trial involved 263 couples seeking treatment for male infertility between December 2021 and December 2023. Couples pursuing ICSI for primary or secondary infertility were included in the study. The outcomes of the ICSI procedure were evaluated across the treatment groups. Results No statistically significant differences were observed between the density gradient group and the refrigeration group in terms of the number of injected oocytes, fertilized oocytes, or fertilization rates. However, the refrigeration group showed a significantly higher number of top-cleaved oocytes and a greater top cleavage rate compared to the density gradient group (p = 0.02). Additionally, the refrigeration group had a significantly higher number of transferred embryos (p < 0.001). Similarly, the selenium group demonstrated a significantly higher number of top-cleaved oocytes and a greater top cleavage rate than the density gradient group (p = 0.04 and p < 0.001, respectively). The number of transferred embryos was also significantly higher in the selenium group compared to the density gradient group. Conclusions  Both refrigeration with an egg yolk buffer and selenium supplementation had significant positive effects on oocyte maturation and embryo development, resulting in higher top cleavage rates and an increased number of transferred embryos. However, pregnancy rates following each technique individually were comparable to those achieved with the density gradient method.